2019
DOI: 10.1016/j.chom.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Redondoviridae, a Family of Small, Circular DNA Viruses of the Human Oro-Respiratory Tract Associated with Periodontitis and Critical Illness

Abstract: In Table S1 of this article as originally published, the wrong sequence was mistakenly included for the pan-HCRV-AA qPCR assay probe during assembly of the table. The table has now been updated with the correct sequence (AAATGGAAGGGAGAGA GGCCTTTGG). This error does not alter the conclusions of the original paper. The authors apologize for any confusion or inconvenience this error may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 0 publications
3
41
0
1
Order By: Relevance
“…We delimited CRESS virus genera using a cutoff of 50% Rep protein identity, following a recent literature example 18 . Genera infecting the same host genus were assigned a Greek number and named with reference to the host (ent for Entamoeba and gia for Giardia) (Supplementary Table 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We delimited CRESS virus genera using a cutoff of 50% Rep protein identity, following a recent literature example 18 . Genera infecting the same host genus were assigned a Greek number and named with reference to the host (ent for Entamoeba and gia for Giardia) (Supplementary Table 8).…”
Section: Resultsmentioning
confidence: 99%
“…Since this is impractical for metagenomically identified viruses, case-control studies are used to reveal associations between viruses and disease. Importantly though, this does not confirm the host; for example, the CRESS virus family Redondoviridae is associated with human periodontal disease and critical illness 18 , but it remains unknown whether the viruses infect humans or a separate host, itself associated with or causing the observed clinical outcomes.…”
mentioning
confidence: 96%
“…A previous study of saliva and pooled dental plaque from a limited number of patients (n = 7) with periodontal disease showed differences in virome composition between healthy/gingivitis/ mild periodontitis patients and those with moderate/severe periodontal disease 20 . Another virome study in humans with limited periodontal samples identified a new family of redondoviridae associated with periodontal disease 31 . Taken in aggregate, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that viruses, including herpes simplex virus-1,2, Epstein-Barr virus, and cytomegalovirus play important roles in periodontal disease [21][22][23][24][25][26][27][28][29] . Also, in recent studies, other different viruses have been associated with periodontal disease, however, a comprehensive evaluation of the oral virome in relationship to periodontal disease using shotgun sequencing has not been carried out in mice and to a limited extent in humans [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…While attempting to study human virome in bronchoalveolar lavage (BAL) samples of lung transplant patients [ 1 , 2 ], Abbas and colleagues identified sequence reads that aligned with low-coverage to a poorly characterized circovirus, named porcine stool-associated circular virus-5 (PoSCV-5) [ 3 ]. Further genomic characterization of these reads revealed that they belonged to a novel virus having a single, closed molecule of circular DNA approximately 3000 nucleotides (nt) in length called Redondovirus (ReDoV) [ 4 ]. It was proposed as the second most prevalent eukaryotic virus, after anelloviruses, in human respiratory samples from viral metagenomics studies.…”
Section: Introductionmentioning
confidence: 99%